Comparative study of the binding mode between cytochrome P450 17A1 and prostate cancer drugs in the absence of haem iron. Issue 16 (2nd November 2019) - Song, Dalong; Zhang, Jihua; Wang, Yuanlin; Hu, Jianxin; Xu, Shuxiong; Xu, Yuangao; Shen, Hujun; Wen, Xiaopeng; Sun, Zhaolin
Abstract: According to the X-ray crystal structures of CYP17A1 (including its complexes with inhibitors), it is shown that a hydrogen bond exists between CYP17A1 and its inhibitors (such as abiraterone and TOK-001). Previous short MD simulations (50 ns) suggested that the binding of abiraterone to CYP17A1 is stronger than that of TOK-001. In this work, by carrying out long atomistic MD simulations (200 ns) of CYP17A1 and its complexes with abiraterone and TOK-001, we observed a binding mode between CYP17A1 and abiraterone, which is different from the binding mode between CYP17A1 and TOK-001. In the case of abiraterone binding, the unfilled volume in the active site cavity increases the freedom of movement of abiraterone within CYP17A1, leading to the collective motions of the helices G and B′ as well as the breaking of hydrogen bond existing between the 3β-OH group of abiraterone and N202 of CYP17A1. However, the unfilled volume in the active site cavity can be occupied by the benzimidazole ring of TOK-001, restraining the motion of TOK-001. By pulling the two inhibitors (abiraterone and TOK-001) out of the binding pocket in CYP17A1, we discovered that abiraterone and TOK-001 were moved from their binding sites to the surface of protein similarly through the channels formed by the helices G and B′. In addition, based on the free energy calculations, one can see that it is energetically favorable for the two inhibitors (abiraterone and TOK-001) to enter into the binding pocket in CYP17A1.